APPLICATION OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING EDUCATION AND ENSURING THE CONTINUITY OF EDUCATION AND EDUCATION (World Bulletin of Physical Education and Sports Science, 2026)
This in the article upbringing science in education modern pedagogical from technologies of use theoretical and practical aspects illuminated. Education and of upbringing unity based on student person every one-sided development, interactive methods, digital tools and innovative approaches upbringing in the process place analysis Also, the national and universal values based on upbringing science effective organization to grow to the issues separately attention focused.
Keywords: Education, pedagogical technologies, interactive methods, digital education, training and upbringing unity, national values.